Spiritual Intelligence in Zanjan Nursing and Midwifery Students and its Related Factors - Parvin Mohebi; Leila Rastegari; Elham Jaafari; Mansoureh Sepehrinia (Zanjan University of Medical Sciences and Health Services, 2013)
Background and Objectives: Spiritual intelligence is an important concept in the field of spirituality. It combines the spirituality and intelligence structures within a new structure. Spirituality helps to better compatibility with the environment. This study investigated the spiritual intelligence of Zanjan Nursing and Midwifery students and assessed its relationship with some demographic factors. Material and Methods: In this correlational study, the intelligence level of 220 students in Nursing and Midwifery school of Zanjan were measured using the Spiritual intelligence questionnaire consisted of 29 items with the Likert scoring scale. The participants were selected using random sampling. The data was analyzed using statistical tests at the significant level of P<0.05 in the SPSS-18. Results: The result of the study revealed that 74.5 percent of the participants were female and 25.5 percent of were male. The mean age of the students was 21.5 (SD=23.2). The mean GPA of the students was 16.68 (SD=19.2). The mean score of Spiritual intelligence of student was 17.42 (SD=121) with a range of 43-145. The average of Spiritual intelligence was 16.9 (SD=122.61) among female students and 18.44 (SD=116.3) among male students. About 83.4 percent of students had good spiritual intelligence, 14.5 percent had average spiritual intelligence, and 1.8 percent of student had low spiritual intelligence. Conclusion: Nursing and midwifery studentshavea high level of spiritual intelligence. Personality characteristics need to be evaluated as predictor of spiritual intelligence.